Sixth International Symposium Monitoring of Mediterranean Coastal Areas. Problems and Measurement Techniques Livorno (Italy) September 28-29, 2016 - Conese, Claudio (Proceedings e report, 2017)
The Sixth International Symposium Monitoring of Mediterranean Coastal Areas. Problems and Measurement Techniques (Livorno, Italy 28-29 September 2016) was organized by the CNR-IBIMET in collaboration with University Departments, the City of Livorno, the LEM Foundation, the Livorno Port Authority and CeSIA-Accademia dei Georgofili, with the patronage by Accademia Nazionale dei Lincei, the Tuscany Region and the Province of Livorno. The Symposium, that every two years addresses to Mediterranean scholars, was characterized by discourse of topics related to Mediterranean coastal areas and by the search for technical and instrumental solutions to problems related to: energy production in the coastal area, morphology and evolution of coastlines, flora and fauna of the littoral system, management and integrated coastal protection, coastline geography, human influence on coastal landscape.